ANALISIS UJI FISIS BRIKET AROMATERAPI BERBAHAN SERAI DAN SERBUK KAYU DENGAN PEREKAT PINUS MERKUSII - Ervina Putri Wulandari; Ety Jumiati; Miftahul Husnah (Indonesian Physics Communication, 2023)
Aromatherapy briquettes have been made as an alternative fuel made from lemon grass, sawdust and pine resin. Composition variations between lemongrass and sawdust (meranti) in samples A (30% : 70%), B (40% : 60%), C (50% : 50%) with 60% pine resin adhesive with drying time 7 days. Physical test parameters carried out: density, moisture content, and heat. The test results showed that the optimum aromatherapy briquettes were sample C which had a density value of 0.954 g/cm3, a moisture content of 7.81% and a calorific value of 8640 cal/g. The value of water content and heating value complies with SNI 01-6235-2000.